Physician Burnout: Historical Context, Psychosomatic Division, Evolution, Results, Solutions, and Recommendations - Carol Nash (Encyclopedia)
Physician burnout is a psychosomatic syndrome that arises from feeling overwhelmed with confronting issues in those with dedication or commitment to their job. It presents with emotional, mental, and physical fatigue that negatively influences patient treatment decisions and care, representing a primary occupational hazard affecting a significant number of these healthcare providers at some point in their career such that there is an urgency to the need for improvement.